The Effectiveness of Somatic, Auditory, Visual, Intellectual (SAVI) Methods in Learning Description Text Writing Skills In Class VII Students of SMP Negeri 24 Makassar - Haris, Muh. Fahrezi; Daeng, Kembong; Asia M, Asia M (Journal of Educational Sciences, 2025)
The aim of this study is to determine the effectiveness of the Somatic, Auditory, Visual, Intellectual (SAVI) method in teaching descriptive text writing skills to seventh-grade students at SMP Negeri 24 Makassar. This research employed an experimental design using the one-group pretest-posttest model. The population of the study consisted of all seventh-grade students at SMP Negeri 24 Makassar. Data collection was carried out through written tests administered before and after the treatment. Data analysis techniques showed that the SAVI method was effective in teaching students' descriptive text writing skills. The results of the Paired Sample T-Test indicated that the t-value for class VII.1 was 10.204 > t-table 2.093, for class VII.2 it was 14.426 > t-table 2.085, and for class VII.4 it was 14.523 > t-table 2.085, with a significance value (Sig. 2-tailed) for all three classes = 0.001 < 0.05, thus H1 was accepted. The average skill in writing descriptive texts among students improved from the "poor" category to the "fair" category.